Review of Pharmacokinetics of Levothyroxine, with Specific Focus on Patient with Thyroid Carcinoma - Vasudev Shenoy (Journal of Global Pharma Technology, 2017)
Total or near to Total thyroidectomy with Radio Iodine treatment is current therapy for Thyroid cancer. Post thyroidectomy the patients are on Levothyroxine as a supplement therapy to maintain the Thyroid hormone levels. Levothyroxine has been considered as a narrow therapeutic index drug. In Thyroid cancer patients, radio-iodine ablation procedure causes hypothyroid state which will be further elongated by the administration of sub optimal doses and hyperthyroid symptoms with higher doses. This article would evaluate the pharmacokinetics of levothyroxine and in specific focus in patients with papillary carcinoma followed with thyroidectomy with Radio iodine treatment.Materials and Methods: The references are review from published literature and web based information.Results: Levothyroxine is considered as a narrow therapeutic index drug and hence individualization of the dose in a particular patient is important for optimal therapeutic effect.Conclusion: Review of pharmacokinetics of levothyroxine in various disease condition, coexisting disease and concomitant medication suggested for optimization of the dose of levothyroxine for avoiding the toxic adverse effects due to hypothyroid or hyperthyroid conditions.